KARAKTERISTIK PENDERITA TIFUS ABDOMINALIS PADA ANAK YANG DIRAWAT INAP DI RSU SUNDARI MEDAN TAHUN 2016 - Isna Hanim; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Based on Riskesdas Sumatera Utara (2007), the proportion of Typhus abdominalis in Medan city is 600 per 100,000 population. In 2016 the proportion of Typhus abdominalis cases in children whom hospitalized at RSU Sundari Medan was 86.6%. The research aims to find out the characteristic of Typhus abdominalis patient in children whom hospitalized at RSU Sundari Medan in 2016. The research is descriptive research with case series design. The population is data of Typhus abdominalis in childrenwhom hospitalized at RSU Sundari Medan was 845 patient data, and the samples is 272 patient data taken by simple random sampling. Data analysis using chi-square test and Mann whitney test. The highest sociodemographic proportions: age group 6-18 years 45,6%, males 55,9%, Islam 89,3%, not school 54,4%, and live in Medan city is 91,9%. Proportion based on clinical symptoms when admitte, the highest symptoms was fever 100.0%, no complication 89.5%, extraintestinal complication type 76,9%, tubex® test lab diagnostic result average score 4.36, average treatment duration 5 , 07 days, not own expense (BPJS, etc) 79,4%, go home treatment 77,2%. There was a significant difference between the average treatment duration based on the source of cost (p = 0.0001). There was a significant difference between the proportion of circumstances at home by source of cost (p = 0.0001). There was a significant difference betweenaverage treatment duration and the proportion of circumstances at home based on source cost. The hospital to further improve the handling of patients with Typhus abdominalis in children so as to reduce the incidence, career cases, and the occurrence of complications, and the hospital medical record to better complement of data patients with Typhus abdominalis such as tribe, education, and complication status. Keywords: Typhus abdominalis, Children 0-18 years old, Characteristics, RSU Sundari Medan